Estimating the household's willingness to pay for the improvement of amenities in the Philippine Eagle Center - Coronel, Jeffrey Jefferson Y.; Mariano, Hanzel P.
This study determined how much the residents of Poblacion, Davao City are willing to pay for the construction of additional amenities for the Philippine Eagle Center. The additional revenue would be used to fund the improvements in facilities in the Philippine Eagle Center and fund its other conservation projects. The study conducted a survey interview to 100 household respondents, which were randomly selected from Poblacion, Davao City. The survey questionnaire used in the study consisted of four parts: introduction, socio-economic and demographic information, reasons for visit, and willingness to pay. The average household size was approximately 6 people with an average household income of P/15, 570. Ninety percent of the respondents have been to the Center with an average of 5 visits. The study suggested improvements in amenities, in particular the renovation of the Visitors Lounge and a Covered Concrete Pathway. The results revealed that 76% of the respondents were willing to pay for the proposed improvement of amenities and the mean WTP value is P10.47 per visit. With the use of the Ordinary Least Squares (OLS) model, it was found that the total household monthly income and the number of visit had greatly influenced the WTP values of the respondents. A household with high monthly income expressed a higher WTP than households with lower income. A household with a greater number of visits expressed a lower WTP than households with lesser number of visits. This could be attributed to the diminishing marginal utility of a person. The study has a small sample size of only 100 and a small adjusted R-squared value.
Thesis, Undergraduate (BS Economics)--University of the Philippines, Mindanao